Strongly Detuned Tunable Photonic Oscillators - Herrera, Daniel J.; Tomkins, Kevin; Valagiannopoulos, Constantinos; Kovanis, Vassilios; Lester, Luke F. (IEEE photonics technology letters, 2021)
A semi-analytical dimensionless formula is presented for predicting the period-one frequency of an optically-injected laser over a wide range of injection powers and positive detunings. The result shows that for any given injected optical power, there exists an optimal detuning at which the period-one frequency is maximized. The formula is applied to a tabletop optical injection system with a commercially-available quantum-well distributed feedback laser with previously unknown design parameters. By extrapolating the linearity of the period-one frequencies at zero-detuning and weak-injection regimes, the physical control parameters of the laser are approximated to the analytical formula for wide ranges of injection powers and positive detunings. The accuracy of the model is experimentally verified, achieving period-one frequencies as high as 84.7 GHz.